PRINCIPLES OF THE FORMATION OF CULTURAL AND HYGIENE SKILLS OF PRESCHOOL CHILDREN - Soliyeva Dilnoza (Journals Park Publishing, 2024)
Methods of formation of cultural and hygiene skills, cultural education-hygiene skills, formation cultural and hygiene skills, food culture.
Keywords: cultural-hygiene, regularity and continuity, hygienic education, general criteria